2000
DOI: 10.1111/j.0014-3820.2000.tb00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Effects and Gender Specialization in a Tropical Heterostylous Shrub

Abstract: Abstract. Male sterility in hermaphroditic species may represent the first step in the evolution toward dioecy. However, gender specialization will not proceed unless the male-sterile individuals compensate for fitness lost through the male function with an increase in fitness through the female function. In the distylous shrub Erythroxylum havanense, thrum plants are partially male-sterile. Using data collected throughout eight years, we investigated whether thrum individuals have an increased performance as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Theoretical and empirical studies have stressed the role of an asymmetrical pollen transfer between floral morphs, and consequently of pollinators, as the main evolutionary force in the process of gender specialization in distylous species (Ganders, 1974;Ornduff, 1975;Charlesworth and Charlesworth, 1979;Lloyd, 1979;Beach, 1981;Barrett, 1992, and references therein). Although intrinsic genetic factors may affect gender specialization in plants (Casper, 1992;Domínguez et al, 1997;Á vila-Sakar and Domínguez, 2000), the nature and intensity of other selective pressures favoring gender specialization has rarely been investigated (Olesen, 1979;Contreras and Ornelas, 1999;Leege and Wolfe, 2002). Yet, because cross-pollination is necessary for reproductive success in both morphs, they should not differ in attributes that contribute to attracting or rewarding floral visitors (Leege and Wolfe, 2002), leading to equal reproductive success.…”
mentioning
confidence: 99%
“…Theoretical and empirical studies have stressed the role of an asymmetrical pollen transfer between floral morphs, and consequently of pollinators, as the main evolutionary force in the process of gender specialization in distylous species (Ganders, 1974;Ornduff, 1975;Charlesworth and Charlesworth, 1979;Lloyd, 1979;Beach, 1981;Barrett, 1992, and references therein). Although intrinsic genetic factors may affect gender specialization in plants (Casper, 1992;Domínguez et al, 1997;Á vila-Sakar and Domínguez, 2000), the nature and intensity of other selective pressures favoring gender specialization has rarely been investigated (Olesen, 1979;Contreras and Ornelas, 1999;Leege and Wolfe, 2002). Yet, because cross-pollination is necessary for reproductive success in both morphs, they should not differ in attributes that contribute to attracting or rewarding floral visitors (Leege and Wolfe, 2002), leading to equal reproductive success.…”
mentioning
confidence: 99%
“…Previous studies have suggested that E. havanense is experiencing a process of gender specialization in which most thrum plants produce twice as much seeds as pins, whereas most pin individuals produce fewer seeds but a higher proportion of viable pollen (Domínguez et al 1997;Avila-Sakar and Domínguez 2000;Rosas et al 2005). Results from this study indicate that the disproportionate damage inflicted by seed predators on thrum individuals is owing to their greater seed production.…”
Section: Discussionmentioning
confidence: 51%
“…2), to only 48% of the total seed crop, a 23% disadvantage. However, even when seed predators may consume up to 52% of the total seed crop of large thrum individuals, plants from this morph still have a fecundity advantage over pin individuals (see also Avila-Sakar and Domínguez 2000;Rosas et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations